The effectiveness of chlorhexidine gluconate mouthwash for recurrent intraoral herpes: A case report - Muhammad A. Farisyi; Riani Setiadhi (Journal of Dentomaxillofacial Science, 2021)
Objective: Recurrent intraoral herpes (RIH) is one of the common oral diseases that causes painful ulcers. Mouthwashes are widely used for prevention and treatment of various oral and dental diseases. Chlorhexidine oral rinses may be useful for controlling intraoral Herpes simplex virus type 1 (HSV-1) infection, related virucidal effects and also inhibition of viral replication. This case report describes the effectiveness of chlorhexidine gluconate mouthwash therapy in patient with RIH. Case Report: A 50-year-old male patient complained of ulcers at lip and tongue since 10 days before, the patient had applied triamcinolone oral paste to the lesion but it did not improved. Oral ulcers frequently repeated and appeared in different places. Intraoral examination showed multiple ulcers at buccal mucosa and dorsum of tongue, as well as scrapable white plaques on tongue. The laboratory examination showed IgG Anti HSV 1 was reactive. RIH was made as the diagnosis, based on clinical and laboratory examination. Results: After 1 month therapy of 0.2% chlorhexidine gluconate mouthwash, vitamin B12, and folic acid the oral lesions were improved. Conclusion: The chlorhexidine mouthwash is effective for RIH therapy in reducing pain and accelerating wound healing.